Keterampilan Menulis Paragraf Mahasiswa Fakultas Ilmu Budaya Universitas Diponegoro Semarang - Sri Puji Astuti (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2018)
Writing skills of paragraph are skills that students must have. This research aims to describe the writing skills of paragraph for students of the English Literature Study Program and the Japanese and Culture Study Program of the Faculty of Cultural Sciences, Diponegoro University in 2017. The research data is in the form of discourse fragments that were made by students.Collecting data used purposive sampling technique. Then the data was identified, classified, and analyzed by using paragraph theory. Based on the results of the study, it can be concluded that the writing skill of paragraphs for students in the English Literature Study Program and Japanese and Culture Study Program still needs to be improved because there were still found paragraphs that are lacking in the unity of the ideas. Likewise,by cohesiveness are still found errors, especially in terms of reference. In terms of completeness, sequence, and consistency of points of view in paragraphs students can apply well.